The Use of Multimedia and its Impact on Bangladeshi EFL Learners at Tertiary Level - Islam, Farzana Sharmin Pamela (International Journal of Language Education, 2020)
As 21st century is the era of modern technologies with different aspects, it offers us to make the best use of them. After tape recorder and overhead projector (OHP), multimedia has become an important part of language classroom facilities for its unique and effective application in delivering and learning lesson. Although in many parts of Bangladesh, a South Asian developing country, where English enjoys the status of a foreign language, the use of multimedia in teaching and learning is viewed as a matter of luxury. However, nowadays the usefulness and the necessity of it are well recognized by the academics as well as the government. The study aims to focus on the difference between a traditional classroom void of multimedia and multimedia equipped classrooms at university level by explaining how multimedia support the students with enhanced opportunity to interact with diverse texts that give them more in-depth comprehension of the subject. It also focuses on audio-visual advantage of multimedia on the students’ English language learning. The study has followed a qualitative method to get an in-depth understanding of the impact of using multimedia in an English language classroom at tertiary level. For this purpose, the data have been collected from two different sources. Firstly, from students’ written response to  an open ended question as to their comparative experience of learning  lessons with and without multimedia facilities; and secondly, through  observation of English language classes at a private university of Dhaka, the capital city of Bangladesh. The discussion of the study is limited to  the use of multimedia in English language classroom using cartoons, images and music with a view to enhance students’ skills in academic writing, critical analysis of image and critical appreciation of music. For this purpose, cartoons in English language, images from Google and music from You Tube have got focused discussion in this paper.